Kangaroo Mother Care: A Simple Method to Care for Low-Birth-Weight Infants in Developing Countries - Akhtar, Khursheda; Haque, Musarrat; Khatoon, Soofia (Journal of Shaheed Suhrawardy Medical College, 2013)
Kangaroo Mother Care (KMC) is an effective way to meet baby's needs for warmth, breastfeeding, protection from infection, stimulation, safety and love. Mother acts as an incubator as kangaroo and put low birth infant vertically in between the chest for warming. The term kangaroo care is derived from practical similarities to marsupial care-giving. The premature infant is kept warm in the maternal pouch and is close to the breasts for unlimited feeding. It provides an alternative to incubator care, without separation from the mother. The importance of KMC in low- and middle-income countries has been highlighted as a contributing factor to the achievement of the Millennium Development Goal 4 that targets a reduction by two-thirds of under-five mortality rates from 1990 to 2015. This programme is mediated by humoral, autonomic and somatic behaviours, expressed ultimately as innate competency in breastfeeding behaviours. It is simple, acceptable to mothers and can be continued at home. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16256 J Shaheed Suhrawardy Med Coll, 2013;5(1):49-54